CALCULATION OF THE AERODYNAMIC COEFFICIENTS USING MATLAB® - Ruiz Lizama, Edgar (2005)
The article presents the calculation of aerodynamic coefficients of an airship wing's design: sustentation and moment coefficient applying two methods of integration. As a theoretical part, the fine theory of the aerodynamic profile is used and as a calculation tool the MATLAB software is used, through programs which are presented in their respective files. Besides, the outcome of results reports are presented.